Development and Validation of RP-HPLC Method for Quantitation of Aviptadil Acetate and its Degradation Products - Al-Saikhan, Fahad I; Al-Shdefat, Ramadan I.; Abd-Elaziz, Mohamed A; Adam, Elsadig H. Kh.; Ahsan, Fakhrul (Asian Journal of Biological and Life Sciences, 2015)
Abstract Pulmonary arterial hypertension (PAH) is a disease of the pulmonary arteries and arterioles that increases the pulmonary vascular resistance and pulmonary artery pressure. Aviptadil, a vasoactive intestinal peptide (VIP), has been suggested as a novel drug for the treatment of idiopathic PAH. In this paper, we developed an HPLC method for quantitating aviptadil and monitoring acid and base catalyzed degradation of the drug. The method was validated according of ICH and US FDA guidelines of HPLC methods. The drug was separated in 4.5±0.1 minutes; the calibration curve was linear over a concentration range between 2 and 10μg/ml (r2 = 0.9996); the recovery was 99.65%; the relative standard deviation (RSD) for intra- and inter-day was < 1.0. Thus the method was simple, accurate, precise, reliable and reproducible. Degradation studies revealed that aviptadil is stable in neutral medium and unstable in both acidic as well as basic media with faster degradation in later.
Keywords: Aviptadil Acetate; Development and validation method; HPLC; Stability